Induction of Phage-Specific Antibodies by Two Therapeutic Staphylococcal Bacteriophages Administered per os - Majewska, Joanna; Kaźmierczak, Zuzanna; Lahutta, Karolina; Lecion, Dorota; Szymczak, Aleksander; Miernikiewicz, Paulina; Drapała, Jarosław; Harhala, Marek; Marek-Bukowiec, Karolina; Jędruchniewicz, Natalia; Owczarek, Barbara; Górski, Andrzej; et al. (Frontiers in Immunology, 2019)
In therapeutic phage applications oral administration is a common and well-accepted delivery route. Phages applied per os may elicit a specific humoral response, which may in turn affect phage activity. We present specific anti-phage antibody induction in mice receiving therapeutic staphylococcal bacteriophage A3R or 676Z in drinking water. The schedule comprised: (1) primary exposure to phages for 100 days, followed by (2) diet without phage for 120 days, and (3) secondary exposure to the same phage for 47 days. Both phages induced specific antibodies in blood (IgM, IgG, IgA), even though poor to ineffective translocation of the phages to blood was observed. IgM reached a maximum on day 22, IgG increased from day 22 until the end of the experiment. Specific IgA in the blood and in the gut were induced simultaneously within about 2 months; the IgA level gradually decreased when phage was removed from the diet. Importantly, phage-specific IgA was the limiting factor for phage activity in the gastrointestinal tract. Multicopy proteins (major capsid protein and tail morphogenetic protein H) contributed significantly to phage immunogenicity (IgG), while the baseplate protein gpORF096 did not induce a significant response. Microbiome composition assessment by next-generation sequencing (NGS) revealed that no important changes correlated with phage treatment.